Study of Modern Human Evolution via Comparative Analysis with the Neanderthal Genome - Musaddeque Ahmed; Ping Liang (Genomics & Informatics)
Many other human species appeared in evolution in the last 6 million years that have not been able to survive to modern times and are broadly known as archaic humans, as opposed to the extant modern humans. It has always been considered fascinating to compare the modern human genome with that of archaic humans to identify modern human-specific sequence variants and figure out those that made modern humans different from their predecessors or cousin species. Neanderthals are the latest humans to become extinct, and many factors made them the best representatives of archaic humans. Even though a number of comparisons have been made sporadically between Neanderthals and modern humans, mostly following a candidate gene approach, the major breakthrough took place with the sequencing of the Neanderthal genome. The initial genome-wide comparison, based on the first draft of the Neanderthal genome, has generated some interesting inferences regarding variations in functional elements that are not shared by the two species and the debated admixture question. However, there are certain other genetic elements that were not included or included at a smaller scale in those studies, and they should be compared comprehensively to better understand the molecular make-up of modern humans and their phenotypic characteristics. Besides briefly discussing the important outcomes of the comparative analyses made so far between modern humans and Neanderthals, we propose that future comparative studies may include retrotransposons, pseudogenes, and conserved non-coding regions, all of which might have played significant roles during the evolution of modern humans.